Muscle wasting in hTNFtg mice, an animal model for rheumatoid arthritis, due to increased cathepsin L expression. (22nd February 2012) - Hayer, Silvia; Willburger, Martin; Niederreiter, Birgit; Jelinek, Aurica; Shvets, Tetyana; Smolen, Josef; Redlich, Kurt
Abstract : Objective: To investigate skeletal myopathy in a chronic inflammatory, erosive animal model for rheumatoid arthritis, the human tumour necrosis factor transgenic (hTNFtg) mice. Methods: To evaluate whether hTNFtg mice are suffering from skeletal muscle atrophy, the authors isolated Triceps surae muscles from hTNFtg animals from various time-points of age starting 4 weeks until 16 weeks after birth. Muscle weight and body weight were assessed from these animals. Muscle tissue, muscle weight and bodyweight from age and sex-matched wildtype animals served as controls. To investigate whether tumour necrosis factor (TNF) blockade protects hTNFtg animals from muscle atrophy, 5 female hTNFtg animals were treated with anti-TNF ab (Infliximab, 10mg/kg, 3x per week, ip). Untreated hTNFtg animals served as controls. To identify proteolysis pathways and pro-inflammatory cytokine expression involved in muscle atrophy, the authors performed quantitative real-time PCR for Cathepsin L, B, S, H, D, MMP-9 and Interleukin (IL)-1 and IL-6 from mRNA isolated from muscle tissues of hTNFtg and wildtype animals. To further investigate infiltration of inflammatory cells, muscle tissue sections are stained for macrophages, neutrophils, T cells and B cells and convential hematoxylin/eosin. Results: The authors demonstrate that hTNFtg mice show significantly less triceps surae muscle weight compared to sex- and age matched wildtype animals. Reductions in muscle weight became already manifest at the early age of 4 weeks and were continuously reduced until week 16. Due to decreased muscle weight, bodyweight was also significantly decreased in hTNFtg animals compared to their wildtype littermates. The authors found a significantly increased mRNA expression levels of Cathepsin L, a lysosomal endopeptidase responsible for muscle protein degradation, in muscles from hTNFtg compared to their wildtype littermates. In contrast, other proteases such as cathepsin B, S, H, D did not reach significantly increased expression levels between these 2 genotypes. Moreover, proinflammatory cytokines such as IL1 and IL6 are also significantly upregulated in muscles from hTNFtg mice. Conclusion: Despite spontaneous development of chronic inflamed, erosive arthritis, chronic overexpression of TNF leads to skeletal muscle atrophy due to increased tissue-degrading cathepsin L in hTNFtg animals.